Analyzing conversational implicatures in a synchronous online class on pragmatics - Jerrymie Mila; Jeanard Anthony Robiego (Yayasan Mitra Persada Nusantara, 2026)
Conversational implicatures are inherent in everyday interaction. Understanding how they emerge in synchronous class discussions can help shape clear communication beyond what is explicitly stated, thus improving class interaction and class management. However, research on conversational implicatures based on Grice’s Cooperative Principle in synchronous class discussions remains limited in Philippine context. Hence, this study aims to analyze conversational implicatures produced by both the teacher and students in a synchronous classroom setting. Data were gathered from verbatim transcripts of teacher-student interactions and analyzed using the framework of Grice’s Cooperative Principle. The findings reveal that both the teacher and students produced conversational implicatures that were highly dependent on the contextual situation, reflecting the dynamic nature of interaction in the online classroom. However, the teacher produced more instances of maxim flouting (18 out of 27), with the Maxims of Quantity and Manner most frequently flouted, often as a strategy to encourage students to think critically and respond independently and at the same time create a less restrictive environment. Students also tended to flout the same maxims (unclear and ambiguous), though less frequently (9 out of 27), particularly during recitations, as a response to the communicative situation (e.g., class participation and peer discussion). In contrast, the Maxims of Quality were less frequently flouted, indicating that participants generally maintained truthfulness in classroom discourse, while there was no instance of Relation flouting. Despite these instances of maxim flouting, both the teacher and students, generally, were able to successfully interpret the intended meanings, demonstrating pragmatic competence in understanding conversational implicatures within classroom interaction. The study also suggests the need for further research examining additional factors and comparing virtual and face-to-face contexts to provide deeper insights into the role of conversational implicature in human interaction.